Removal material for radioactive material astatine-211

A fibrous activated carbon-based removal material supporting 1,4-diazabicyclo[2.2.2]octane or alkali metal iodides addresses the inefficiencies in astatine-211 collection, achieving high removal efficiencies and ensuring a safe environment during astatine-211 handling.

JP2024176255APending Publication Date: 2024-12-19THE UNIV OF TOKYO +2
View PDF 1 Cites 0 Cited by

Patent Information

Application Number
JP2023094683
Authority / Receiving Office
JP · JP
Patent Type
Applications
Current Assignee / Owner
Filing Date
2023-06-08
Publication Date
2024-12-19

AI Technical Summary

Technical Problem

Existing technologies lack an efficient material for collecting and cleaning astatine-211, which is a short-lived alpha-emitting nuclide used in cancer therapy, to prevent its dispersion and minimize internal radiation exposure during handling and production.

Method used

A removal material composed of fibrous activated carbon supporting 1,4-diazabicyclo[2.2.2]octane or alkali metal iodides, with specific properties such as fiber diameter, surface area, and bulk density, to achieve high collection efficiency.

Benefits of technology

The material effectively absorbs astatine-211, reducing its concentration and creating a safer indoor environment by achieving collection efficiencies of 97.0% or more, particularly 99.0% in certain configurations.

✦ Generated by Eureka AI based on patent content.

Smart Images

  • Figure 2024176255000001_ABST
    Figure 2024176255000001_ABST
Patent Text Reader

Abstract

To provide a removal material for efficiently capturing astatine-211 dispersed indoors during the production or utilization of pharmaceuticals containing astatine-211, thereby purifying the room.SOLUTION: A removal material for radioactive material astatine-211 comprises at least one chemical substance selected from the group consisting of 1,4-diazabicyclo[2.2.2]octane and alkali metal iodides, carried onto a porous material predominantly composed of activated carbon. Preferably, the quantity of the chemical substance carried is 0.3×10-3-3.0×10-3 mol per gram of activated carbon. Preferably, the porous material is fibrous activated carbon with a fiber diameter of 10-25 μm, and the specific surface area of the fibrous activated carbon is 1000-2000 m2 / g as measured by the BET method.SELECTED DRAWING: Figure 2
Need to check novelty before this filing date? Find Prior Art

Description

[Technical field]

[0001] The present invention relates to a material for removing the radioactive substance astatine-211 with excellent collection efficiency. [Background technology]

[0002] In recent years, alpha-particle-emitting nuclides have been attracting attention as cancer treatment drugs. These radiations have a short range, so they can selectively attack only the targeted cancer cells while minimizing the impact on normal cells. Among alpha-particle-emitting nuclides, astatine-211, which has a short half-life, is the most promising radioactive substance.

[0003] The drug using astatine-211 is bismuth-209( 209 Bi) into cyclotron-generated helium-4( 4 He) is irradiated to create the 209 Bi( 4 He,2n) 211 Astatine-211 is obtained by the nuclear reaction of 1,2-trimethylsilane (At). In this nuclear reaction, in addition to the production of astatine-211, various impurity nuclides are also produced. Therefore, in order to use astatine-211, only astatine-211 is separated from the irradiated material, and the resulting astatine-211 is dissolved in ethanol and placed in a V-vial, after which the ethanol is removed to solidify it and transport it to the location where it will be used. During this separation process, the handling of ethanol, and the handling of the resulting reagent, astatine-211 may disperse into the air and contaminate the room. Furthermore, if the air in the room is inhaled, there is a risk of serious internal exposure.

[0004] In order to address this problem, an exhaust filter is provided in a facility that produces astatine-211 to prevent the astatine-211 from diffusing outside the system (see Patent Document 1). However, Patent Document 1 does not provide any specific proposal regarding the configuration or material of a filter that has excellent astatine-211 collection efficiency. Meanwhile, Patent Document 2 uses anhydrous sodium sulfate or activated carbon as an exhaust filter for preventing astatine from diffusing in a similar manner. However, a filter with such a configuration does not have sufficient astatine-211 collection efficiency, and there is room for improvement. [Prior art documents] [Patent documents]

[0005] [Patent Document 1] Patent Publication No. 2021-92483 [Patent Document 2] Republished Publication No. 2019 / 176585 Summary of the Invention [Problem to be solved by the invention]

[0006] The present invention has been devised to solve the above-mentioned problems of the prior art, and its object is to provide a removal material for efficiently collecting astatine-211 that is dispersed indoors when producing or using a chemical containing astatine-211, thereby purifying the indoor space. [Means for solving the problem]

[0007] In order to achieve this object, the present inventors have conducted extensive research into configurations and materials that have excellent collection efficiency for astatine-211, and have discovered that 1,4-diazabicyclo[2.2.2]octane and alkali metal iodides exhibit high adsorption capacity for astatine-211, and that astatine-211 can be removed with high collection efficiency by using a removal material in which either of these chemical substances is supported in a suitable manner on a porous material whose main component is activated carbon, thereby completing the present invention.

[0008] That is, the present invention has the following configurations (1) to (5). (1) A material for removing the radioactive substance astatine-211, characterized in that it is composed of a porous material whose main component is activated carbon and which supports at least one chemical substance selected from the group consisting of 1,4-diazabicyclo[2.2.2]octane and alkali metal iodides. (2) The amount of chemicals supported by the porous material is 0.3 × 10 per 1 g of activated carbon. -3 ~3.0×10 -3 mol. (3) The porous material is a fibrous activated carbon having a fiber diameter of 10 to 25 μm, and the specific surface area of ​​the fibrous activated carbon by the BET method is 1000 to 2000 m 2 / g. (4) The bulk density of the radioactive astatine-211 removal material is 0.05 to 0.30 g / cm 3 The radioactive astatine-211 removal material according to (3), (5) The radioactive astatine-211 removing material according to (4), characterized in that the radioactive astatine-211 removing material is a sheet-like material having a thickness of 1.0 to 15 mm. Effect of the Invention

[0009] The radioactive astatine-211 removal material of the present invention can be installed in rooms or facilities where astatine-211 is generated or used to effectively absorb astatine-211 and reduce its concentration in the system, thereby providing a safe indoor environment. [Brief description of the drawings]

[0010] [Figure 1] FIG. 1 shows a schematic diagram of an example of a pleated filter using the astatine-211 removal material of the present invention. [Diagram 2] FIG. 1 shows a schematic diagram of an example of a room and an exhaust box when the astatine-211 removal material of the present invention is used. [Diagram 3] FIG. 1 shows a schematic diagram of an evaluation device for astatine-211 capture efficiency used in the examples. DETAILED DESCRIPTION OF THE PREFERRED EMBODIMENTS

[0011] The radioactive astatine-211 removal material of the present invention is a material that can efficiently adsorb and remove astatine-211 that has leaked into a system such as a cyclotron or other facility that generates radioisotopes, or a laboratory that uses radioactive materials. In particular, the astatine-211 removal material of the present invention is composed of a porous material mainly composed of activated carbon, carrying at least one chemical substance selected from the group consisting of 1,4-diazabicyclo[2.2.2]octane and alkali metal iodides.

[0012] The porous material used in the present invention is one whose main component is activated carbon. Here, the main component means that it contains 50% by weight or more, preferably 70% by weight or more, more preferably 80% by weight or more, and particularly preferably 90% by weight or more. In addition to activated carbon, the porous material can contain inorganic adsorbents such as zeolite, and organic porous materials composed of styrene-divinylbenzene copolymers.

[0013] Activated carbon is suitable as a gas phase filter material because it has a large surface area that contributes to adsorption and is highly moldable compared to other adsorption materials, such as ceramics mainly composed of zeolite or metal oxides, and organic porous materials obtained by styrene-divinylbenzene copolymerization. Activated carbon can be in the form of granules, powder, granulated powder, or fiber, but in the present invention, it is preferable to use fibrous activated carbon. Fibrous activated carbon is characterized by a high adsorption rate at a high adsorption rate, and can obtain the same collection efficiency as powdered or granular activated carbon under conditions where the loading amount per unit volume is smaller.

[0014] The fiber diameter of the fibrous activated carbon used is preferably 10 to 25 μm. Since the fibrous activated carbon can obtain a higher removal efficiency when the geometric surface area per unit volume is larger, the fiber diameter is more preferably 22 μm or less, and further preferably 20 μm or less. If the fiber diameter is less than the lower limit, the weight yield is reduced when the fiber is fired and carbonized, and the strength after firing is extremely reduced, which may make it difficult to manufacture the filter thereafter. On the other hand, if the fiber diameter is larger than the upper limit, it becomes difficult to diffuse the pyrolysis substances out of the fiber due to the pyrolysis during firing and carbonization, and the fiber after firing may become brittle.

[0015] The specific surface area of ​​the fibrous activated carbon used for nitrogen adsorption by the BET method is 1000 m 2 / g or more, especially 1200m 2 / g or more, 2000m 2 / g or less. If the specific surface area is less than the lower limit, the pore size becomes too small, and the pores may be blocked by the supported chemical substance, resulting in a decrease in adsorption capacity. If the specific surface area exceeds the upper limit, there is no particular problem with performance, but the yield during production of activated carbon becomes extremely low, making it unrealistic in terms of strength and cost.

[0016] Although it is possible to adsorb astatine-211 to a certain extent using activated carbon alone, the adsorption characteristics are not stable, and the removal rate is generally low when the average is taken. Therefore, the present invention is characterized in that a chemical substance selected from the group consisting of 1,4-diazabicyclo[2.2.2]octane and alkali metal iodides is supported on a porous material mainly composed of activated carbon. By supporting these chemical substances, a stable and high adsorption amount of astatine-211 can be achieved. Potassium iodide and sodium iodide are suitable as alkali metal iodides. The supported amount of these chemical substances varies depending on the supported substance and the specific surface area of ​​the activated carbon fiber used, but is generally 0.3 x 10 per 1 g of activated carbon fiber. -3 mol or more, preferably 0.4×10 ―3 mol or more, 3.0×10 -3If the amount is less than the lower limit, the adsorption of astatine-211 and the reaction with the chemical substance may not be carried out efficiently, whereas if the amount is more than the upper limit, the pores in the fibrous activated carbon may be blocked by the chemical substance, making it difficult to carry out adsorption, resulting in a decrease in collection efficiency.

[0017] The astatine-211 removal material of the present invention in the form of fibers can be used by packing it in a column as it is in the form of a cotton, or it can be formed into a sheet for use. The bulk density of the astatine-211 removal material of the present invention when packed in a column or formed into a sheet is 0.05 g / cm3 in terms of breathability and handling. 3 Above, especially 0.06g / cm 3 More than 0.30g / cm 3 It is preferable that the bulk density is less than the lower limit. If the bulk density is less than the lower limit, a considerable packing height is required to obtain a certain collection efficiency, and it takes up a lot of space when used as a filter, which is not very practical. If the bulk density is greater than the upper limit, the breathability may be extremely reduced and the filter may not be suitable for use.

[0018] The astatine-211 removal material of the present invention can be used by forming it into a sheet such as a nonwoven fabric, woven fabric, or knitted fabric. The environment in which astatine-211 is generated and leaks is expected to be a wide area such as a building or room, rather than a local area, and ventilation with a high air volume is required, which can be easily achieved by forming it into a sheet. The thickness of the astatine-211 removal material of the present invention in the form of a sheet is preferably 1.0 mm or more, particularly 1.2 mm or more and 15 mm or less. The thickness and bulk density of the sheet are optimally designed according to the filling amount for the space that can be used as a pleated filter and the air volume to be treated, but if the thickness is less than the lower limit, the sheet is too thin and may be difficult to mold as a filter.

[0019] An example of a filter that uses a sheet-like removal material is one that incorporates a pleated filter as shown in Figure 1. Specifically, a plurality of sheet-like removal materials are prepared as filter media 2 by folding them in a zigzag pattern to form pleats, and spacers 1 for rectifying the flow are inserted between the pleats. These are then framed in a frame 3, allowing the filter to be used as a packaged filter.

[0020] A typical example of the method for producing the astatine-211 removal material of the present invention is as follows. First, fibrous activated carbon is obtained by carbonizing and activating the raw material of activated carbon, for example, cellulose-based fibers such as rayon, cupra, and cotton, polyacrylonitrile-based, novoloid-based, polyvinyl alcohol-based, and pitch-based fibers, by a known method. To make this into a sheet, for example, the raw material fiber may be made into a sheet such as a nonwoven fabric or woven fabric in advance, and then carbonized and activated. Alternatively, the raw material fiber, in this case long or short fibers, may be carbonized and activated to obtain a sheet by a known method. The cotton-like fibrous activated carbon may be mixed with short fibers of natural or synthetic fibers or adhesive components to form a paper. Next, the obtained fibrous activated carbon is supported with chemical substances such as 1,4-diazabicyclo[2.2.2]octane and / or alkali metal iodide. The loading method is generally a method of immersing fibrous activated carbon in a solution in which a chemical substance is dissolved and drying it, but there is no particular limitation as long as the method can uniformly load the chemical substance on the fiber surface. In the present invention, the loading amount is calculated by measuring the dry weight before and after loading, subtracting the measured weight before loading from the measured weight after loading, and converting the result into moles from the molecular weight to calculate the number of moles per weight before loading.

[0021] The method of using the astatine-211 removal material of the present invention includes a method of removing astatine-211 by installing a packed column filled with the removal material near the source of astatine-211, or a method of removing astatine-211 by attaching a removal material molded as a pleated filter to an exhaust box for exhausting polluted air in a room. As the latter method, FIG. 2 shows a schematic diagram of a room and an exhaust box. As shown in FIG. 2, polluted air 6 containing astatine-211 generated from a source 5 in a room 4 is forcibly exhausted through an exhaust box consisting of a pleated filter 7, a dust filter 8, and an exhaust fan 9 in FIG. 1 from an exhaust duct 10, thereby effectively removing astatine-211. Alternatively, astatine-211 can be removed by a method that does not rely on blowing air, such as hanging or attaching a sheet-like removal material alone to a polluted room, especially to a wall (11A) or ceiling (11B).

[0022] The astatine-211 removal material of the present invention, configured as described above, can achieve an astatine-211 collection efficiency of 97.0% or more, further 98.0% or more, or even 99.0% or more, according to the measurement method of the Examples. EXAMPLES

[0023] The effects of the present invention will be shown in the following examples, but the present invention is not limited to these examples and can be modified and implemented without departing from the spirit of the present invention. The property values ​​in the examples were evaluated according to the following methods.

[0024] (1) Fiber diameter The samples were photographed at 500 to 1000 times magnification using a scanning electron microscope or an optical microscope, and the fiber diameter was measured using a vernier caliper.

[0025] (2) Bulk density A sample with a diameter of 50 mm was cut out, dried by heating at 100°C for 1 hour, and weighed after leaving it in a desiccator overnight. This measurement was converted to weight per unit area and divided by the thickness to obtain the thickness.

[0026] (3) Thickness (2) The bulk density of the 50 mm diameter sample was 0.147 N / cm 2 The load was measured using a dial gauge.

[0027] (4) Specific surface area The adsorption isotherm was calculated from the nitrogen adsorption isotherm at liquid nitrogen temperature (relative pressure 0.02-0.2) by the BET method.

[0028] (5) Astatine-211 capture efficiency The evaluation device shown in FIG. 3 was used. The evaluation device is composed of a sample holder 13 for mounting the sample set 12, an acrylic box 14, a V-vial 15 containing astatine-211, and a pressure-resistant tube 16 for connecting the suction pump and the sample holder. The sample was punched out to a size of 60 mm in diameter, and the dust removal filter (QR-100: manufactured by Advantec Toyo) 17, six pieces of sample 18, and a backup filter CHC-50 (manufactured by Advantec Toyo) 19 were mounted on the sample holder 13 as the sample set 12 in this order from the upstream side. The effective diameter of this sample set 12 during ventilation is 50 mm. The sample holder 13 was attached to the upper opening of an acrylic box 14 with dimensions of 32 cm wide, 32 cm deep, and 29 cm high on the upstream side, and a suction pump was attached to the downstream side via the pressure-resistant tube 16. The V-vial 15 containing the ethanol in which astatine-211 was dissolved was opened in the acrylic box 14, and the suction pump was started to aerate the sample at an air volume of 29 L / min for about 3 hours. The radioactivity of astatine-211 was measured for each sample using a gamma counter (PerkinElmer WIZARD2). The collection efficiency of the sample was calculated by dividing the count value of the most upstream sample out of the six samples 18 by the total count value of the three upstream samples.

[0029] Example 1 Weight 205g / m 2 , thickness 3.0mm, specific surface area 1520m 2 / g, fibrous activated carbon nonwoven fabric with fiber diameter of 13 μm (bulk density 0.068 g / cm 3) was immersed in 0.9 × 10 -3 The sample was prepared by loading mol / g.

[0030] Example 2 Weight 198g / m 2 , thickness 2.8mm, specific surface area 1510m 2 / g, fibrous activated carbon nonwoven fabric with fiber diameter of 18 μm (bulk density 0.071 g / cm 3 ) was immersed in 0.9 × 10 -3 The sample was prepared by loading mol / g.

[0031] Example 3 The same fibrous activated carbon nonwoven fabric used in Example 1 was soaked with 0.9×10 sodium iodide. -3 The sample was prepared by loading mol / g.

[0032] Example 4 The same fibrous activated carbon nonwoven fabric as used in Example 1 was soaked with 0.9 × 10 potassium iodide. -3 The sample was prepared by loading mol / g.

[0033] Example 5 Weight 210g / m 2 , thickness 2.9mm, specific surface area 1270m 2 / g, fibrous activated carbon nonwoven fabric with a fiber diameter of 18 μm (0.072 g / m 3 ) was immersed in 0.9 × 10 -3 The sample was prepared by loading mol / g.

[0034] Example 6 The same fibrous activated carbon nonwoven fabric as used in Example 1 was soaked with 0.5 × 10 potassium iodide. -3 The sample was prepared by loading mol / g.

[0035] Example 7 Weight 150g / m 2 , thickness 4.0mm, specific surface area 1270m 2 / g, fibrous activated carbon nonwoven fabric with a fiber diameter of 18 μm (0.038 g / cm 3 ) was immersed in 0.9 × 10 -3 The sample was prepared by loading mol / g.

[0036] Example 8 Weight 220g / m 2 , thickness 3.2mm, specific surface area 850m 2 / g, fibrous activated carbon nonwoven fabric with a fiber diameter of 20 μm (0.068 g / m 3 ) was immersed in 0.9 × 10 -3 The sample was prepared by loading mol / g.

[0037] Comparative Example 1 The same fibrous activated carbon nonwoven fabric as used in Example 1, but without any chemical substances attached thereto, was used as a sample.

[0038] Comparative Example 2 The same fibrous activated carbon nonwoven fabric used in Example 1 was soaked with 0.9×10 sodium chloride. -3 The sample was prepared by loading mol / g.

[0039] Comparative Example 3 The same fibrous activated carbon nonwoven fabric used in Example 1 was soaked with 0.9×10 sodium bromide. -3 The sample was prepared by loading mol / g.

[0040] The details and evaluation results of the samples of Examples 1 to 8 and Comparative Examples 1 to 3 are shown in Table 1 below.

[0041] [Table 1]

[0042] As can be seen from Table 1, the removal materials of Examples 1 to 8, which satisfy the requirements of the present invention, exhibited an astatine-211 capture efficiency of 98.0% or more, and in particular, the removal materials of Examples 1 to 6 exhibited a high astatine-211 capture efficiency of over 99.0%. On the other hand, the removal materials of the present invention that do not support a chemical substance exhibited an astatine-211 capture efficiency inferior to Examples 1 to 8. [Industrial Applicability]

[0043] The astatine-211 removal material of the present invention is extremely useful in the industry because it can effectively absorb astatine-211 and reduce the concentration in the system by being installed in a room or facility where astatine-211 is generated or used, thereby providing a safe indoor environment. [Explanation of symbols]

[0044] 1 Spacer 2 Filter media 3 Frame material 4 Indoor 5. Sources of Astatine-211 6. Air containing astatine-211 diffused indoors 7 Pleated Filter 8 Dust removal filter 9 Fan 10 Exhaust duct 11A Sheet-shaped material removal material (wall surface) 11B Sheet-shaped material removal (ceiling) 12 Sample Sets 13 Sample Holder 14 Acrylic Box 15V vial 16 Pressure resistant tube 17 Dust removal filter media 18 Samples (6 sheets) 19 Backup Holder

Claims

1. A material for removing the radioactive substance astatine-211, characterized in that it is constructed by supporting at least one chemical substance selected from the group consisting of 1,4-diazabicyclo[2.2.2]octane and alkali metal iodides on a porous material mainly composed of activated carbon.

2. The amount of chemical substance supported in the porous material is 0.3 × 10 per 1 g of activated carbon. -3 ~3.0 x 10 -3 2. The radioactive astatine-211 removal material according to claim 1, characterized in that it is mol.

3. The porous material is a fibrous activated carbon having a fiber diameter of 10 to 25 μm, and the specific surface area of ​​the fibrous activated carbon measured by the BET method is 1000 to 2000 m 2 The radioactive astatine-211 removal material according to claim 2, characterized in that the astatine-211 removal material has a molecular weight of 1000 to 10000.

4. The bulk density of the radioactive astatine-211 removal material is 0.05 to 0.30 g / cm 3 The radioactive astatine-211 removal material according to claim 3,

5. 5. The radioactive astatine-211 removal material according to claim 4, characterized in that the radioactive astatine-211 removal material is in the form of a sheet having a thickness of 1.0 to 15 mm.

Citation Information

Patent Citations

  • Producing method and device for astatine isotope, and separation / recovery method and device for astatine isotope

    JP2021092483A